Assessing the effects of gut bacteria manipulation on the development of the oriental fruit fly, Bactrocera dorsalis (Diptera; Tephritidae) - Kanjana Khaeso (2018)
© 2017, Springer Science+Business Media Dordrecht. Bactrocera dorsalis (Diptera: Tephritidae) is a serious menace to agricultural production worldwide. In order to prevent further damage, it is of paramount important that cost-effective strategies should be developed for their management. Gut bacteria has established diverse relationships with their insect hosts, which could be exploited in pest management programs to improve on control efficiency. In this study, gut bacteria isolates identified by culture dependent technique were incorporated into larval diets in an attempt to understand the roles they play in the development and survival of oriental fruit fly. From our results, the isolated bacteria belonged to four different phyla including the Firmicutes, Proteobacteria, Bacteroidetes and Actinobacteria. The response of the fly to different gut isolates varied greatly. Diets enriched with Enterococcus phoeniculicola had lower larval developmental duration, higher pupal weight, and an increased percentage survival. On the other hand, diets supplemented with Lactobacillus lactis had negative effects on B. dorsalis development. This study provides clues on how symbiotic bacteria could be exploited in mass rearing for an efficient implementation of the Sterile Insect Technique (SIT) in pest management programs.